Seasonal Poverty Incidence and Determinants among Vegetable Farm Households in Ogun State, Nigeria - Olumayowa, Oyebanjo; Adetolani , Amokaye; Akerele, Ezekiel Olaoluwa; Dada, Omolara M. (Acta Universitatis Danubius. Œconomica, 2023)
Farmers are often prone to poverty due to low income and insufficient credit during production season. This study examined seasonal poverty incidence and determinants among vegetable farmers. Panel data were collected from 192 respondents through multistage sampling using structured questionnaire. Data were analysed using descriptive statistics, Foster-Greer-Thorbecke poverty index and Logit model. Poverty line shows that 67.2% of the respondents were poor during planting season and 25.5% during post-harvest season. The poor household heads include 51-60 years-old (90.9%), widow(er) (100%), those without formal education (100%), households with ≥10 members (100%) and those cultivating ≤ 1.0 hectare (90.0%). Logit model revealed that age, marital status and agricultural credit significantly reduced poverty at 5%, 10% and 1% respectively while sex (1%), low education (1%), farming experience (1%), farm size (5%) and dependency ratio (5%) influenced household poverty. Major production constraints include low market price (85%), agricultural credit (76.0%), pilferage (74.0%) and high input prices (73.4%). In conclusion, there is higher likelihood for farm households to be poor during planting season. Therefore, increased agricultural credit should be granted to farmers towards planting season. Modern inputs should be distributed effectively at affordable prices with extension services in order to reduce seasonal poverty.